Silk-Ion Jelly: a highly ion conducting fibrous material - Rana, S. (2012)
In this work, a thin, flexible and mechanically stable polymer conducting material (Silk-Ion Jelly) was developed though application of Ion Jelly on to silk fabrics. Ion Jelly was prepared through jellification of a room temperature ionic liquid, 1-butyl-3-methyl-imidazolium dicyanamide ([bmim][dca]) using gelatin and water and applied to silk fabrics using two different processes: impregnation and in-situ. Silk-Ion Jelly prepared using optimized conditions showed excellent mechanical stability and possess high room temperature conductivity (2.9×10-3 S. cm-1), similar to [bmim][dca] and therefore, this novel ion conducting material may find potential applications in various electrochemical devices due to its eco-friendly preparation route using biomaterials and green solvents.